The Early Impact of Covid-19 on Job Losses among Black Women in the United States. Issue 1 (3rd April 2021) - Holder, Michelle; Jones, Janelle; Masterson, Thomas
ABSTRACT: Given that a high proportion of workers in "essential" sectors of the US economy are Black women, this paper seeks to answer the following: in which occupations did Black women in the US experience the greatest job losses during the early phase of the pandemic? Drawing on feminist economic and stratification economic theories, this quantitative analysis suggests that the greatest losses were cashier jobs in the hotel and restaurant industry, and childcare worker positions in the healthcare and social services industry. These two occupations are low wage, dominated by women, and considered essential. This study posits that Black women disproportionately lost these jobs for three reasons: (1) Black women's strong attachment to the US workforce; (2) Black women's overrepresentation in the hotel/restaurant and healthcare/social services industries; and (3) women's overrepresentation in low-wage occupations. The study offers policy solutions that could help sustain the Black community during the pandemic-inspired economic downturn. HIGHLIGHTS Black women face occupational segregation that is specific to both their gender and their race. Black women's employment is more narrowly concentrated by industry than any other demographic group. Job losses due to COVID-19 especially hit industries in which Black women are concentrated. Black women lost the most jobs in the cashier occupation. Any pandemic-recovery policy agenda must include full employment for Black women.